Twenty-five Years of PTHrP Progress from Cancer Hormone to Multifunctional Cytokine - McCauley, Laurie K. (J Bone Miner Res, 2012)
Twenty-five years ago a ‘new’ protein was identified from cancers that caused hypercalcemia. It was credited for its ability to mimic parathyroid hormone, and hence was termed parathyroid hormone-related protein (PTHrP). Today it is recognized for its widespread distribution, its endocrine, paracrine, and intracrine modes of action driving numerous physiologic and pathologic conditions with a central role in organogenesis. The multiple biological activities within a complex molecule with paracrine modulation of adjacent target cells present boundless possibilities. The protein structure of PTHrP has been traced, dissected and deleted comprehensively and conditionally, yet numerous questions lurk in its past that will carry into the future. Issues of the variable segments of the protein including the enigmatic nuclear localization sequence are only recently being clarified. Aspects of PTHrP production and action in the menacing condition of cancer are emerging as dichotomies that may represent intended temporal actions of PTHrP. Relative to PTH, the hormone regulating calcium homeostasis, PTHrP ‘controls the show’ locally at the PTH/PTHrP receptor throughout the body. Great strides have been made in our understanding of PTHrP actions, yet years of exciting investigation and discovery are imminent.